USING OF TIKTOK FOR PUBLICIZING IMAGE OF THUNG SONG MUNICIPALITY - Kantaboon, Korrakoch (Journal of MCU Nakhondhat, 2024)
This article aims TikTok’s communication with the technique of making short video clips that can answer the problem of perception of the image of local government organizations to the public. The objectives of this research were to study 1) Content for TikTok’s communication to for Publicizing image of Thung Song Municipality. 2) Approaches for providing learning of TikTok’s communication to for Publicizing image of Thung Song Municipality. This was qualitative research based on in-depth interviews with 5 key informants, Director of the Strategy and Budget Division, Head of Public Relations Department, Public Relations Officer. The results showed that 1) Content issues of communication TikTok included the creation of communication content that can effectively promote the image of Thung Song Municipality as a well-recognized organization. The communication content must present the organization’s image in the most positive light possible, conveying its needs, achievements, news, knowledge, and vision to the public in a manner that is both informative and beneficial. The goal is to ensure that the public gains a clear understanding of the organization’s work and accomplishments. The content includes personnel, organizational operations, services, policies, and performance outcomes, 2) Approaches for providing learning of TikTok are involves the creation of communication through video clips aimed at disseminating information that effectively enhances the public image of Thung Song Municipality. The communication style is intended to be both simple and humorous, making the content memorable and easily accessible to a broad audience. The focus is on generating valuable and engaging content. The content includes communication that effectively reaches the target audience, engaging content, and communication strategies for producing memorable video clips.